Trends in good laboratory practice studies submitted for the marketing authorization of pharmaceuticals in Japan - Oku, Yusuke; Someya, Hitoshi (Frontiers in Pharmacology, 2025)
Pharmaceuticals and Medical Devices Agencies (PMDA) receives the non-clinical safety studies following Good Laboratory Practice (GLP) for the marketing authorization of medical products. Here we analyzed the trends of GLP-compliant non-clinical studies (GLP studies) submitted to PMDA from FY2017 to FY2023. Geographical analysis of the origin of studies revealed that the share of Japanese studies slightly decreased over years, reflecting the drug lag/loss in Japan. This was supported by the analysis of the time from the completion of GLP studies to submissions. Importantly, studies from China and Taiwan were emerging, reflecting the active drug development in China, which is not the adherent to the OECD Mutual Acceptance of Data (MAD). We also discuss the PMDA’s policies on the GLP studies conducted in non-MAD countries.